PENINGKATAN KAPASITAS PENGELOLAAN KEUANGAN DAN STRATEGI PEMASARAN DIGITAL BAGI PENGURUS BUMDES DI KABUPATEN KATINGAN - Nahan, Noorjaya; Abdi, Muhamad Ruzaini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Community service activities (pkm) have a strategic role in increasing the capacity of human resources (HR), especially in the field of human resource management in the village government and village-owned enterprises (bumdes). Strengthening the competence of village officials through training is one of the real approaches in overcoming the problem of weak organizational management and village finances. One of the key factors for the success of the training program in PKM is the support from superiors or organizational leaders. This support not only encourages participation in training, but also ensures the sustainability of the implementation of training results in the field. HR management in training urgently needs the support of superiors through encouragement, discussion of training objectives, and providing opportunities for the application of skills that have a significant effect on the effectiveness of training transfer to the work environment. In the context of training village financial managers, the involvement of village heads or local leaders as a form of implementation of human resource management is a strategic aspect to create sustainable changes in work behavior. This review emphasizes that the integration of institutional support is an important part of human resource development through community-based training activities.